MY SAY: Putting back the pieces for peace - Abd Razak, Dzulkifli (2010)
The International Day of Peace (IDP) is celebrated every year on Sept 21. This year, it is directed at young people — the generation that will become the leaders of the future and who will ensure that peace will prevail. In the words of UN Secretary General Ban Ki-moon: "Help us to work for peace. You are impatient. You see what we, your elders, allow to persist, year after year: poverty and hunger; injustice and impunity; environmental degradation."